Leaf and Petiole Extract of Centella Asiatica are Potential for Antifertility and Antimicrobial Material - Amilah, Susie; Sukarjati, Sukarjati; Rachmatin, Diaz P; Masruroh, Masruroh (Folia Medica Indonesiana, 2019)
Ethanol extract of leaves and petiole of pegagan (Centella asiatica) is potential as antimicrobial and antifertility. This study was to investigate whether ethanol extracts of leaf and petiole of Centella asiatica has potential as an antimicrobial and can decrease sperm quality and spermatogenic cells of mice. This was a randomized controlled study using Centella asiatica plant from which we made ethanol extract. The extract of the leaves and petiole of Centella asiatica was subjected to antimicrobial test using the bacteria S. aureus, S. epidermidis, and A. aerogenes. Then the observation was done after a 24-hour-old bacterial cultures by measuring the diameter of the clear zone in mm. Thereafter, the extract was given to randomly grouped mice that were divided into two groups receiving the leaf extract in one group and the petiole exract in another for 35 days. On day 36 the mice were sacrificed for spermatozoa quality and testicular histology examination. Statistical analyses used in this study were ANOVA and LSD tests. There was inhibition zone difference between leaf and petiole (p=0.000). Inhibition zone between bacteria S. epidermidis, S. aureus and A. aerogenes showed no difference (p=0.198). Inter-dose inhibition zone showed difference (p=0.000). Centella asiatica leaf extract showed inhibition zone better than that of Centella asiatica petiole extract. In spermatozoa quality test, there was effect of Centella asiatica leaf extract on sperm motility (p<0.05), viability (p<0.05), morphology (p<0.05) and concentration (p<0.05). No effect of pegagan petiole extract was found on sperm motility (p<0.05), viability (p<0.05), abnormal morphology (p<0.05) and concentration (p<0.05). Highest degradation of spermatozoa quality was obtained from Centella asiatica petiole extract at a concentration of 150 mg/kg bw. Spermatogenic cell test results showed no effect of Centella asiatica leaf extract in decreasing spermatogonia (p=0.000), spermatocytes (p=0.000), and spermatids (p=0.000) counts. No effect of pegagan petiole extract in decreasing the number of spermatogonia, spermatocytes and spermatids. The highest reduction spermatogenic cells of seminiferous tubules was obtained by Centella asiatica petiole extract in a concentration of 150 mg/kg bw. In conclusion: Centella asiatica leaf and petiole extract has antimicrobial potency as contra-ceptives